The communicative role of caregivers assisting stroke patients from Sincelejo, Colombia - Lastre-Meza, Karina; Anaya-Paternina, Laura Vanessa; Contreras-Dales, Ana Beatriz (Universidad y Salud, 2025)
Introduction: Cerebrovascular diseases are a public health problem affecting the different capabilities of patients, including communication. Thus, caregivers play a fundamental role in their recovery. Objective: To describe the communicative role of caregivers in the support of patients with stroke sequelae in the city of Sincelejo, Colombia. Materials and methods: A positivist paradigm, quantitative approach, and descriptive cross-sectional study was carried out with 40 caregivers, who were selected according to criteria sampling and chain recruitment. A sociodemographic survey about favorability and communicative well-being as well as the Likert Scale were applied. A reliability and internal consistency analysis was conducted. Results: The majority of caregivers were women. Informal caregivers, with high school education, and belonging to low socioeconomic status were also predominant. A positive attitude regarding competences such as being and knowing what to do; appropriate treatment of patients, with justice and respect, were observed as common features. The knowledge competence was considered unfavorable, which was characterized by limited understanding regarding pathology, strategies used, and insufficient skills, techniques, and abilities to fulfill their functions. Conclusions: Caregivers of stroke patients should be qualified through programs that improve the being, knowing, and knowing how to do competencies.